PENGARUH PEMBERIAN REBUSAN BAYAM MERAH TERHADAP PENINGKATAN KADAR HB PADA IBU HAMIL TRIMESTER II DENGAN ANEMIA DI KLINIK KURNIA DELI TUA TAHUN 2022 - Stefani Anastasia Sitepu (JURNAL ILMIAH DHDT - KEBIDANAN, 2022)
Anemia of pregnancy is a condition of decreased hemoglobin content in the blood of pregnant women, which is a health problem, especially in developing countries with high morbidity rates in pregnant women. The causes of anemia are the occurrence of hemodilution during pregnancy, the lack of iron content in the food consumed, and the presence of some content from food or drink that interferes with the absorption of iron in the body. One alternative that can be done to meet the iron needs of pregnant women is to consume vegetables that contain iron, one of which is red spinach. The purpose of this study was to determine the effect of red spinach stew on increasing Hb levels in pregnant women in the second trimester with anemia at the Kurnia Deli Tua Clinic.The research method used is Pre-experimental Design with One Group Pretest-Postest research design. The study population of pregnant women in the second trimester with anemia was 16 people. Samples were taken using total sampling with a total sample of 16 pregnant women in the second trimester with anemia. Independent Variable Decoction of red spinach the dependent variable is the increase in Hb levels in pregnant women. Research instrument Easy Touch GCHb Hemoglobin check tool and slow observation.The results of the study using the Wilcoxon test found a p value of 0.003 < 0.05, which means that there is an effect of giving red spinach stew on increasing Hb levels in pregnant women in the second trimester with anemia at the Kurnia Deli Tua clinic in 2022.